2009
DOI: 10.1186/1297-9686-41-51
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of genomic breeding values in multi-breed dairy cattle populations

Abstract: BackgroundTwo key findings from genomic selection experiments are 1) the reference population used must be very large to subsequently predict accurate genomic estimated breeding values (GEBV), and 2) prediction equations derived in one breed do not predict accurate GEBV when applied to other breeds. Both findings are a problem for breeds where the number of individuals in the reference population is limited. A multi-breed reference population is a potential solution, and here we investigate the accuracies of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
409
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(466 citation statements)
references
References 21 publications
40
409
2
6
Order By: Relevance
“…Heritability estimates for average litter size obtained with the PED model were 0.21, 0.14 and 0.19 for A, B and AB lines, respectively. Reliabilities of genome-based predictions of fertility traits in dairy cattle have been lower than those obtained for more heritable traits, such as milk production and composition (Hayes et al, 2009). Nevertheless, several authors have argued that genome-based prediction could be of special interest for increasing rate of genetic gain for lowly heritable traits if a sufficiently large number of records per individual is available for training the models (Ibañ ez-Escriche and GonzalezRecio, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Heritability estimates for average litter size obtained with the PED model were 0.21, 0.14 and 0.19 for A, B and AB lines, respectively. Reliabilities of genome-based predictions of fertility traits in dairy cattle have been lower than those obtained for more heritable traits, such as milk production and composition (Hayes et al, 2009). Nevertheless, several authors have argued that genome-based prediction could be of special interest for increasing rate of genetic gain for lowly heritable traits if a sufficiently large number of records per individual is available for training the models (Ibañ ez-Escriche and GonzalezRecio, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies on GEBV accuracy/reliability estimated from real data have been reported in the literature for cattle with GEBV reliabilities ranging from 18% to 78% (Harris et al, 2009;VanRaden et al, 2009;Hayes et al, 2009b), fewer are reported for sheep. Our GEBV accuracies are similar to others obtained using a medium-density markers chip of 15% to 79% for wool traits in Merino sheep (Daetwyler et al, 2010a), and 7% to 31% for carcass and meat-quality traits in multi-breed sheep data (Daetwyler et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the accuracy of GEBV has been evaluated in experiments involving several livestock species, such as dairy (Harris et al, 2009;Hayes et al, 2009b) and beef (Saatchi et al, 2011) cattle populations, chicken (González-Recio et al, 2009) and sheep (Daetwyler et al, 2010a(Daetwyler et al, , 2012a(Daetwyler et al, , 2012bDuchemin et al, 2012). Apart from the study by Kemper et al (2011), the use of high-density genomic information to select for nematode resistance in sheep has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to evaluate the reliabilities of the genomic predictions in the same population from which breeding candidates are being selected. Reliabilities based on real data have been reported from Holstein populations (Hayes et al, 2009a;VanRaden et al, 2009;Harris and Johnson, 2010;Lund et al, 2010; -E-mail: jrt@vikinggenetics.com Su et al, 2010) and Jersey populations (Hayes et al, 2009b;Harris and Johnson, 2010).…”
Section: Introductionmentioning
confidence: 99%